Application of selective non-catalytic reduction of NOx in small-scale combustion systems - Abul Hossain, Khandoker; Mohd Jaafar, Mohammad Nazri; Mustafa, Azeman; Appalanidu, Kiran Babu; Ani, Farid Nasir (Elsevier, 2004)
The selective non-catalytic reduction of NOx has been studied experimentally employing commercial grade urea in a pilot-scale diesel-ï¬?red tunnel furnace at 3â€“4% excess oxygen level and with low ppm of baseline NOx ranging from 65 to 75 ppm within the investigated temperature range. The furnace simulated the thermal behavior of small-scale combustion systems such as small capacity boilers, water heaters, oil heaters, etc., where the operating temperatures remain within the range of 950â€“1300 K. NOx reductions were studied with the variation of injection temperature, residence time, normalized stoichiometric ratio (NSR) of the reagent, etc. With 5% urea solution, at an NSR of 4, as much as 54% reduction was achieved at 1128 K. The result is quite signiï¬?cant, especially for the investigated level of baseline NOx. The ammonia slip measurements showed that the slip was below 16 ppm at NSR of 4 and optimum temperature of NOx reduction. Finally, the investigations have demonstrated that selective non-catalytic reduction process is quite applicable to the small-scale combustion applications.